Guselkumab for treatment of moderate-to-severe plaque psoriasis: real-life effectiveness and drug-survival for up to 148 weeks. (3rd April 2023) - Galluzzo, Marco; Marcelli, Lorenzo; Vellucci, Laura; Paganini, Claudia; Maffei, Virginia; Tofani, Lorenzo; Belcastro, Alfredo; Bianchi, Luca; Talamonti, Marina
ABSTRACT: Background: Real-world data are useful to guide the management of psoriasis. Here, we present data on the effectiveness and survival of guselkumab in moderate-to-severe chronic plaque psoriasis for up to 148 weeks. Research design and methods: Cross-sectional study of 122 patients receiving guselkumab (100 mg at weeks 0 and 4, and then every 8 weeks thereafter) for>12 weeks, from November 2018 to April 2022. Main outcome measures: Clinical features and drug survival were analyzed up to 148 weeks. Results: Obese patients (32.8%) and those receiving prior biologics (64.8%) were included. Guselkumab treatment was associated with a rapid decrease in PASI, from 16.2 to 3.2 at week 12, and long-term improvements in all subgroups (97.6%, 82.9%, and 63.4% of patients, respectively, achieved PASI 75, 90, and 100 after 148 weeks). More non-obese than obese patients achieved PASI 100 at week 148 (86.4% vs 38.9%), as did bio-naïve vs bio-experienced patients (86.7% vs 50.0%). Previous biologic therapy was a negative prognostic factor for achieving PASI 100 over the long-term by multivariate analysis ( p  = 0.005). Overall, 96% of patients were on treatment after 2 years. Conclusions: Real-world data confirm the long-term effectiveness of guselkumab in patients with psoriasis.